Ugly Bugs - Arnold, Nick (Horrible Science, 2008)
Science with even more squishy bits left in! Horrible Science is getting a make-over! With a fantastic new cover look and extra horrible bits at the back of the book, these best-selling titles are sure to be a huge hit with a new generation of Horrible Science readers.